Tofacitinib Decreases Autophagy of Fibroblast-Like Synoviocytes From Rheumatoid Arthritis Patients - Vomero, M.; Caliste, M.; Barbati, C.; Speziali, M.; Celia, A. I.; Ucci, F.; Ciancarella, C.; Putro, E.; Colasanti, T.; Buoncuore, G.; Corsiero, E.; Bombardieri, M.; et al. (Frontiers in Pharmacology, 2022)
The pathway of Janus tyrosine kinases (JAKs) has a central role in the pathogenesis of Rheumatoid Arthritis (RA) by regulating multiple immune functions and cytokine production. The JAK inhibitor tofacitinib is effective in RA patients not responding to methotrexate or TNF-inhibitors. Since hyperactive autophagy has been associated with impaired apoptosis of RA fibroblast-like synoviocytes (FLS), we aimed to investigate the role of tofacitinib in modulating autophagy and apoptosis in these cells. FLS isolated from RA biopsies were cultured with tofacitinib in presence of autophagy inducer rapamycin and in serum deprivation condition. Levels of autophagy, apoptosis, and citrullinated proteins were analyzed by western blot, flow cytometry, immunocytofluorescence, and Real-Time PCR. Rapamycin induced an increase in RA-FLS autophagy while the levels of autophagy marker LC3-II were reduced after in vitro treatment with tofacitinib. The analysis of autophagic flux by specific fluorescence dye confirmed the reduction of autophagy in RA FLS. The treatment with tofacitinib did not influence apoptosis of RA FLS. Modulation of the autophagic process by tofacitinib did not significantly change citrullination. The results of this study demonstrate that tofacitinib is able to modulate autophagy of FLS contributing to its effectiveness in RA patients.